Information Seeking Behaviour of Electronic Document and Records Management Systems (EDRMS) Users: Implications for Records Management Practices, Part 3 - Joseph, Pauline; Klobas, J.; Anderson, K. (Records Management Association of Australia, 2008)
This series has studied whether the way RM professionals manage records in accordance with the ISO 15489 standard is consistent with the information seeking behaviour (ISB) of Electronic Document and Records Management Systems (EDRMS) users. In this the final article in the series, the authors report their research findings.